Financial literacy in MSME sector the case of food-based enterprises in Davao City, Philippines - Manalo, Raisa Katrina B. (2017)
Financial literary is widespread not only among students and consumers but also in micro, small and medium enterprises (MSMEs). The low level of financial literary (FL) among entrepreneurs resulted to financial constraints in which MSMEs face financial statement-related problems, and difficulties in accessing loans. It was suggested that FL may resolve the challenges of MSMEs in accessing financial products from financial institutions because it empowers entrepreneurship with sufficient knowledge and skills to make better financial decisions and effective financial management. This study measures the FL, both the basic knowledge and application dimension, of the managers/owners of food-based MSMEs that are situated in the first district of Davao City, Philippines. Subsequent to this, their efficiency level in financial practices related to debt management. The fair level of FL indicated that managers/owners have access to financial services but have poor financial trainings which implied that financial knowledge was not formally practiced in their business. Significant factors that were seen to have affects in FL were sex, educational level, financial training and financial practices of managers/owners such as ownership of savings account and investing. Moreover, the application dimension of FL was identified to have a positive relationship on efficiency in financial practices related to debt management thus, this study suggest that managers/owners should aim for a sound FL both in the knowledge and application dimension.